THE SPECIFICITY OF REPRESENTATION OF THE CONCEPT PUBLIC RELATIONS BY PHRASEOLOGICAL MEANS IN TEACHING MODERN ENGLISHAT HIGHER-EDUCATIONAL INSTITUTIONS: ITS INTERCULTURAL AND SOCIOCULTURAL SIGNIFICANCE - Berdalieva, D.N.; Smanova, G.I. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
Public relations, which arose due to technological progress and as a result of it, is the achievement of universal culture as the level of civilization of human society as a whole, since culture, as a set of achievements in production, social and mental relations in the field of education, science, art and spiritual life, also includes elements of technocratic transformations. Thus, PR is already a cultural practice in itselfand teaching them at higher- educational institutions may assist students to become familiar with the target language and with the culture of studied language much deeper.
Keywords: public relations; cultural conflict; message management; public affairs; social significance of PR